Reproductive Health of the Female Population and Ways to Optimize Obstetric and Gynecological Care at the Level of Primary Health Care - Najmutdinova D. K.; Juraeva G. T. (International Journal on Integrated Education, 2022)
The study assessed the knowledge of primary care among visiting nurses (VN) on the topics: reproductive health and law, contraception and family planning, antenatal care (ANC), prevention of cervical cancer, sexually transmitted diseases (STD) and human immunodeficiency virus (HIV). Based on the results of the assessment, it can be concluded that it is necessary to improve the qualifications of VN for severe conditions in obstetrics. It is necessary to develop protocols for the management of ANC of pregnant and reproductive health for primary care, in particular VN, taking into account their working conditions.